Facing Frederick : the life of Frederick Douglass, a monumental American man - Bolden, Tonya (Abrams Books for Young Readers, 2017)
Coretta Scott King Honor winner Bolden sheds light on new research and interpretations of one of America's most influential African Americans, focusing on Douglass the man rather than the historical icon. Full color and archival images.